ANALISIS DESAIN EKSIBISI MUSEUM DIGITAL HOLTIKULTURA DI KABUPATEN PURWAKARTA - Said Bambang Nurcahya; Dematria Pringgabayu; Nana Sujana; Andri Nurdiyansah (LPPM Politeknik Pajajaran ICB Bandung, 2023)
The digital agro-educational holiculture tourism museum in Purwakarta Regency has designed a digital exhibition, Visual Reality (VR) and Augmented Reality (AR) technology to try to display cultural and educational tourism in the space using advanced technology and can pamper visitors while providing learning about horticulture. In communicating agro-educational audiovisual equipment and interiors that support the creation of an animated atmosphere combined with the conditions for seeding vegetable plants, fruit plants, ornamental plants, and biopharmaceutical plants in Purwakarta Regency, so that visitors can learn, see, and feel, and enjoy both inside museums or in a plantation area of ​​10 hectares in the tourist area of ​​Giri Harja Tajug Gede, Cikopo Village, Bungursari District, Purwakarta Regency. The technique of presenting animated images of plants combined with artificial interiors creates a virtual biosphere that will amaze visitors. In this research the method used is a descriptive method which will describe the process of analyzing digital exhibition designs and recommendations in making detailed engineering designs for Diorama Horticulture, especially related to the use of audiovisual effect technology. 3D animation of horticulture and a trip to the Harja Mukti park